2012
DOI: 10.1080/03643107.2011.604402
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Crevasse Between Direct Practice Social Work and Management by Increasing the Transferability of Core Skills

Abstract: The following is a conceptual article that critically examines a longstanding concern in social work administration that involves the promotion of social workers primarily educated for and employed in direct service or clinical positions to entry or middle management levels. A review of the literature identifies four core skills commonly learned in graduate foundational courses and whose applicability could be expanded, making them more relevant to management. The analysis provides specific suggestions to grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The findings of the current study are consistent with the researchers' collective perception of the overall lack of leadership skills and preparedness of social workers to meet the challenges of the profession (e.g., Austin et al, 2011;Knee & Folsom, 2012;Peters, 2017). No relevant studies focused on the intersection of either interpersonal or problem-solving skills and leadership outcomes to compare and discuss with the results of this research have been found, but both the theoretical literature and empirical research confirm that these two types of skills underpinning social work practice are well incorporated into the social work curriculum (e.g., Gockel & Burton, 2014;Sheppard, & Charles, 2017;Trevithick, Richards, Ruch, & Moss, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The findings of the current study are consistent with the researchers' collective perception of the overall lack of leadership skills and preparedness of social workers to meet the challenges of the profession (e.g., Austin et al, 2011;Knee & Folsom, 2012;Peters, 2017). No relevant studies focused on the intersection of either interpersonal or problem-solving skills and leadership outcomes to compare and discuss with the results of this research have been found, but both the theoretical literature and empirical research confirm that these two types of skills underpinning social work practice are well incorporated into the social work curriculum (e.g., Gockel & Burton, 2014;Sheppard, & Charles, 2017;Trevithick, Richards, Ruch, & Moss, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…A few studies discussed models and styles used within social work leadership within academic settings (Call, Owens, & Vincent, 2013;Randle, 2016), the impact of a taught course on the social change model of leadership (Iachini, Cross, & Freedman, 2015) and students' professional identity (Fronek, Fowler, & Clark, 2011). Social work researchers noted the lack of leadership curriculum both at undergraduate and postgraduate levels (Knee & Folsom, 2012) and leadership training for practicing social workers (Austin, Regan, Samples, Schwartz, & Carnochan, 2011), especially those in general practice, as the reasons for the conspicuous scarcity of social workers in senior administrative positions (Austin & Ezell, 2004;Knee & Folsom, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nor is this inappropriate so long as the supervisor's needs do not undermine a worker's capacity to find their own solutions or prevent them grappling with dilemmas which have no clear answer. In contrast to those who argue that key skills are transferable from social work practice into management roles (Coulshed & Mullender, 2006;Tolleson Knee & Folsom, 2012), Saltiel (2017, p.546) identifies the "limited usefulness" of managers' practice experience suggesting that different attributes are required to promote reflection and analysis on the part of their supervisees. Resisting the tendency to move too swiftly into problem-solving mode is shown to be difficult even for experienced managers who value reflective supervision (Wilkins et al 2017), and it can be particularly challenging to acknowledge doubt and uncertainty when still trying to prove one's own worth as a supervisor.…”
Section: Developmental Models and Transition From Practice To The Supmentioning
confidence: 99%
“…For example, micro practitioners utilize the macro skills when they delegate responsibilities to staff, communicate the organization's mission to the public, supervise direct-service staff, manage collegial relationships, advocate for clients and systems change, and lead teams and committees. Similarly, macro practitioners develop and maintain significant relationships with individuals when they facilitate board and committee meetings, assess and diagnose organizational and community problems, engage in hiring interviews, employ interventions to create positive change, encounter resistance when proposing change, and counsel and coach employees through active listening (Menefee, 2009;Sheafor et al, 2000;Tolleson Knee, 2014;Tolleson Knee & Folsom, 2012). To effectively manage clients, caseloads, programs, and diverse groups of people in differing contexts, micro and macro practitioners rely on a common set of crossover skills, as highlighted in Figure 1.…”
Section: Core Crossover Skillsmentioning
confidence: 99%